2015
DOI: 10.1371/journal.pone.0124946
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidogenic Propensity of a Natural Variant of Human Apolipoprotein A-I: Stability and Interaction with Ligands

Abstract: A number of naturally occurring mutations of human apolipoprotein A-I (apoA-I) have been associated with hereditary amyloidoses. The molecular mechanisms involved in amyloid-associated pathology remain largely unknown. Here we examined the effects of the Arg173Pro point mutation in apoA-I on the structure, stability, and aggregation propensity, as well as on the ability to bind to putative ligands. Our results indicate that the mutation induces a drastic loss of stability, and a lower efficiency to bind to pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 50 publications
6
37
0
5
Order By: Relevance
“…In this study, we examined the effects of heparin on amyloid fibril formation by the N-terminal 1-83 fragment of apoA-I variants, G26R and W50R. The W50R mutation located in the second amyloidogenic segment of the N-terminal region was shown to perturb conformation and stability of full-length apoA-I, which is expected to trigger the formation of amyloid fibrils [23,24]. Our results showed that heparin indeed accelerates the fibril formation of apoA-I 1-83 fragment, especially in the W50R variant, by facilitating b-transition and fibril formation of the highly amyloidogenic region located in residues 44-65.…”
Section: Abstract: Amyloid; Apolipoprotein A-i; Heparinmentioning
confidence: 99%
“…In this study, we examined the effects of heparin on amyloid fibril formation by the N-terminal 1-83 fragment of apoA-I variants, G26R and W50R. The W50R mutation located in the second amyloidogenic segment of the N-terminal region was shown to perturb conformation and stability of full-length apoA-I, which is expected to trigger the formation of amyloid fibrils [23,24]. Our results showed that heparin indeed accelerates the fibril formation of apoA-I 1-83 fragment, especially in the W50R variant, by facilitating b-transition and fibril formation of the highly amyloidogenic region located in residues 44-65.…”
Section: Abstract: Amyloid; Apolipoprotein A-i; Heparinmentioning
confidence: 99%
“…Hence, charge inversion such as Glu34Lys is expected to alter electrostatic interactions not only among apoA-I molecules, thus altering protein solubility, but also between apoA-I and other molecules. For example, negatively charged heparan sulphate proteoglycans are expected to interact more favorably with the more electropositive Glu34Lys variant, potentially leading to increased local concentration of the variant protein and augmenting its deposition in the extracellular matrix of tissues (Rosu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The quenching constant K was calculated from a linear plot of the Stern-Volmer equation as: where fa is the fraction of the initial fluorescence which is accessible to the quencher, K is the Stern-Volmer quenching constant of the accessible fraction and [Q] is the concentration of the quencher. F 0 is the initial fluorescence in the absence of quencher and ΔF is the remaining fluorescence after the addition of acrylamide at each concentration [22][15].…”
Section: Methodsmentioning
confidence: 99%
“…Only rare exceptions were observed within a few mutants including W50R, in which amyloid deposits were found in glomeruli, either confined [13], or expanded to medulla. Previous works from our and other groups have demonstrated that the single point mutations described for apoA-I decrease the marginal protein stability and elicit the tendency to aggregate; even though the conformational shift in the variants is usually subtle under physiological pH and low concentration, it could also induce alterations of the binding to ligands or the eliciting of pro-inflammatory cellular events [14][15]. In order to extend the knowledge about structural motifs that could be involved in apoA-I aggregation and pathogenicity, we herein studied and described the structural initial events that could result in high ?…”
Section: Introductionmentioning
confidence: 99%